2018
DOI: 10.24193/jssp.2018.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Model of Slum Area Management Based on Socio-Spatial Approach. The Case of Baubau City, Indonesia

Abstract: K e y w o r d s: spatial planning, slum, socio-spatial, fuzzy MCDM, DPSIR, Indonesia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Coastal settlements are areas susceptible to change, both natural and changes caused by human activity, the socio-spatial conditions and characteristics of people suggest that the environmental phenomenon of society can shape and transform coastal slums. Meanwhile, space -based policies and physical settlements often conflict with the real conditions of society (Zain et al, 2018).…”
Section: Abstrakmentioning
confidence: 99%
“…Coastal settlements are areas susceptible to change, both natural and changes caused by human activity, the socio-spatial conditions and characteristics of people suggest that the environmental phenomenon of society can shape and transform coastal slums. Meanwhile, space -based policies and physical settlements often conflict with the real conditions of society (Zain et al, 2018).…”
Section: Abstrakmentioning
confidence: 99%
“…The general aim of KOTAKU Program is to provide a decent life for all slums citizens in Indonesian cities (Cheema, 2020) and develop human resources economically and socially to enhance community welfare (Rohimat, Rahmawat, & Seran, 2018). The program also tackles the needs for social and human development (Zain, Salman, & Baja, 2018).…”
Section: A Scopementioning
confidence: 99%
“…The result is also in line with (Badmos et al, 2020) that discovered a factor influenced the choice of residence for slum was markets adjacency. Zain et al, (2018) in his research indicated that engaging space for the development of the trade and services area had an impact on the growth of slums.…”
Section: Cluster and Outlier Analysismentioning
confidence: 99%
“…The expansion of an area or space interm of developing trade and services is proportional to the growth of slums which could also escalate regional microeconomic growth, where slum dwellers operate small-scale businesses (Zain et al, 2018). Slums are growing near strategic areas including business centers, trade, markets, or industries (Badmos et al, 2020;Prianto & Amalia, 2019;Zain et al, 2018).…”
Section: Cluster and Outlier Analysismentioning
confidence: 99%
See 1 more Smart Citation